Specificity of the rapid rK39 antigen-based immunochromatographic test Kalazar Detect(r) in patients with cutaneous leishmaniasis in Brazil - Molinet, Félix Javier León (2013)
The aim of this study was to evaluate the specificity of a rapid immunochromatographic test that was developed to detect antibodies against the rK39 antigen for the diagnosis of visceral leishmaniasis (VL). This evaluation was performed using sera from patients with a confirmed diagnosis of active cutaneous leishmaniasis. The sera from 272 patients with a confirmed diagnosis of localised cutaneous leishmaniasis (CL) who resided in an area endemic for Leishmania braziliensis in Brazil were obtained before the initiation of antileishmanial treatment. Kalazar Detect(r)(InBios, Seattle, WA) recombinant K39 antigen-based immunochromatographic strips were used according to the manufacturer's instructions. The test results were evaluated independently by two examiners in sequential order. The positive controls for the test included five serum samples from five patients with parasitologically confirmed diagnosis of VL caused by Leishmania infantum in Brazil. Overall, 100% of the samples obtained from patients with CL were negative, confirming the absence of a serological cross-reaction for individuals with cutaneous disease when these patients were evaluated using the rapid test. The lack of a cross-reaction in patients who were infected by parasites of the same genus highlights the specificity of the rK39 antigen for the diagnosis of VL in areas with the sympatric circulation of L. braziliensis and L. infantum.